Adult Granulosa Cell Tumor With High-grade Transformation: Report of a Series With FOXL2 Mutation Analysis. (September 2019) - Fashedemi, Yinka; Coutts, Michael; Wise, Olga; Bonhomme, Benjamin; Baker, Gavin; Kelly, Paul J.; Soubeyran, Isabelle; Catherwood, Mark A.; Croce, Sabrina; McCluggage, W. Glenn
Abstract : Adult granulosa cell tumor (AGCT) is a low-grade malignant neoplasm with a significant propensity for late recurrence and metastasis. Almost all AGCTs are composed of cells with bland nuclear features and even when these tumors recur or metastasize, the nuclear features are almost always low-grade. We report 5 cases of AGCT in patients aged 37 to 88 years composed of areas of typical AGCT with low-grade morphology admixed with areas of high-grade morphology, with marked nuclear atypia, often with bizarre multinucleate cells and high mitotic activity; this is the first reported series of high-grade transformation in AGCTs. The high-grade areas often morphologically closely resembled juvenile granulosa cell tumor with abundant eosinophilic cytoplasm, significant mitotic activity, and intermediate sized follicles. Four cases were FIGO stage IA at diagnosis and 1 was stage IIIC with omental involvement. FOXL2 mutation analysis of both the morphologically low-grade and high-grade areas in 4 of 5 cases confirmed the presence of missense point mutation, c.402C>G, p.(Cys134Trp), providing conclusive evidence that the high-grade component represents transformation of typical AGCT rather than the coexistence of another sex cord-stromal tumor, such as juvenile granulosa cell tumor, which has been suggested for such neoplasms. In 3 of 4 cases where immunohistochemistry was undertaken, there was a striking difference between the p53 staining in the low-grade and high-grade components with wild-type staining in the former and diffuse mutation-type immunoreactivity in the latter, suggesting that TP53 mutation is likely to play a role in high-grade transformation. TP53 mutation analysis covering exons 4 to 10 was undertaken in 4 cases and TP53 mutations were identified in the high-grade component of 2 of the cases. In 1 case, there was diffuse block-type p16 staining in the high-grade component. Follow-up in the 4 stage IA neoplasms revealed no evidence of tumor recurrence in 3 (6 to 9 mo follow-up) while the other patient developed mediastinal, peritoneal, and pulmonary metastasis 17 months after diagnosis. High-grade transformation is uncommon in AGCTs and given that one of our cases was advanced stage at diagnosis, another exhibited widespread metastasis within a short period and there have been occasional case reports of aggressive behavior in AGCTs with high-grade transformation, this event may herald an aggressive clinical course.